Single tube gene synthesis by phosphoramidate chemical ligation - El-Sagheer, A; Brown, T (Royal Society of Chemistry, 2017)
Templated chemical ligation of 5′-amino and 3′-phosphate oligonucleotides was used to synthesise a 762 base pair gene for green fluorescent protein. The phosphoramidate linkage can be read by DNA polymerase and transcribed to make RNA. We also show that phosphoramidate ligation and orthogonal CuAAC-mediated DNA ligation can be used simultaneously.